A Review of Cognitive Outcomes Across Movement Disorder Patients Undergoing Deep Brain Stimulation - Cernera, Stephanie; Okun, Michael S.; Gunduz, Aysegul (Frontiers in Neurology, 2019)
Introduction: Although the benefit in motor symptoms for well-selected patients with deep brain stimulation (DBS) has been established, cognitive declines associated with DBS can produce suboptimal clinical responses. Small decrements in cognition can lead to profound effects on quality of life. The growth of indications, the expansion of surgical targets, the increasing complexity of devices, and recent changes in stimulation paradigms have all collectively drawn attention to the need for re-evaluation of DBS related cognitive outcomes. Methods: To address the impact of cognitive changes following DBS, we performed a literature review using PubMed. We searched for articles focused on DBS and cognition. We extracted information about the disease, target, number of patients, assessment of time points, cognitive battery, and clinical outcomes. Diseases included were dystonia, Tourette syndrome (TS), essential tremor (ET), and Parkinson’s disease (PD). Results: DBS was associated with mild cognitive issues even when rigorous patient selection was employed. Dystonia studies reported stable or improved cognitive scores, however one study using reliable change indices indicated decrements in sustained attention. Additionally, DBS outcomes were convoluted with changes in medication dose, alleviation of motor symptoms, and learning effects. In the largest, prospective TS study, an improvement in attentional skills was noted, whereas smaller studies reported variable declines across several cognitive domains. Although, most studies reported stable cognitive outcomes. ET studies largely demonstrated deficits in verbal fluency, which had variable responses depending on stimulation setting. Recently, studies have focused beyond the ventral intermediate nucleus, including the post-subthalamic area and zona incerta. For PD, the cognitive results were heterogeneous, although deficits in verbal fluency were consistent and related to the micro-lesion effect. Conclusion: Post-DBS cognitive issues can impact both motor and quality of life outcomes. The underlying pathophysiology of cognitive changes post-DBS and the identification of pathways underpinning declines will require further investigation. Future studies should employ careful methodological designs. Patient specific analyses will be helpful to differentiate the effects of medications, DBS and the underlying disease state, including disease progression. Disease progression is often an underappreciated factor that is important to post-DBS cognitive issues.